The Prosumer's Role as a Driver of Energy Transition: A Study of Individual Power Producers in Jakarta, Indonesia - Noviyanto, Harfiyan -; Sobirin, Ridwan - (International Journal of Computer and Information System (IJCIS), 2025)
The transition to a sustainable energy system is an urgent priority at both global and national levels, aligning with Indonesia's target of achieving Net Zero Emissions (NZE) by 2060. Within this transition, the phenomenon of the "prosumer"—an individual who not only consumes but also produces energy, primarily through Rooftop Solar Power Plants (PLTS Atap)—has emerged. This study aims to conduct an in-depth analysis of the strategic role of prosumers within the metropolitan context of Jakarta using a techno-social approach. The methodology integrates a techno-economic assessment with social, policy, and user behavior dimensions. A primary focus is placed on the significant regulatory shift from the Ministry of Energy and Mineral Resources (MEMR) Regulation No. 26/2021, which featured a net-metering scheme, to MEMR Regulation No. 2/2024, which eliminates compensation for energy exported to the grid. This change fundamentally alters the prosumer's position from an active contributor of grid energy to a participant focused on optimizing self-consumption. Consequently, the integration of supporting technologies such as Battery Energy Storage Systems (BESS) and Home Energy Management Systems (HEMS) becomes critical to achieving system economic viability. The key finding of this study is that the success of prosumers as transition agents is highly dependent on the stability and supportiveness of public policy. Without consistent and favorable regulations, the strategic potential of prosumers to accelerate energy decentralization in Indonesia is at risk of remaining underdeveloped. Keywords: prosumer, energy transition, rooftop solar PV, techno-social, energy policy.